7x+11=15+3x

Simple and best practice solution for 7x+11=15+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+11=15+3x equation:


Simplifying
7x + 11 = 15 + 3x

Reorder the terms:
11 + 7x = 15 + 3x

Solving
11 + 7x = 15 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
11 + 7x + -3x = 15 + 3x + -3x

Combine like terms: 7x + -3x = 4x
11 + 4x = 15 + 3x + -3x

Combine like terms: 3x + -3x = 0
11 + 4x = 15 + 0
11 + 4x = 15

Add '-11' to each side of the equation.
11 + -11 + 4x = 15 + -11

Combine like terms: 11 + -11 = 0
0 + 4x = 15 + -11
4x = 15 + -11

Combine like terms: 15 + -11 = 4
4x = 4

Divide each side by '4'.
x = 1

Simplifying
x = 1

See similar equations:

| 144x-80=8x+40 | | 9n-12=3n | | 175.00+2.00(50)= | | (9n-12)=(3n) | | 3x^2+25x=28 | | ((6099000-1000000)/6099000)*100 | | -4r+21=-7(5-4r)-8 | | 25+249+100=350 | | 0.48=log(x) | | 10x+20y=230 | | (6x+2)-16=3x | | 25+350+249=100 | | 5-2/x=8 | | 3xsquare+x=14 | | 0.1x=1.5 | | 2x+13=-9x-20 | | 9(x+13)=9x+117 | | 15+7x=8(x-2) | | 5x-3(y)=22 | | -2q+4q=0 | | -1/7x=-8 | | 5(2)-3(-2-2)=22 | | 124/12 | | 10+2x=8(x-2) | | 0.4(x-3)=0.6x+1.8 | | 4(x+2)=4(x+15) | | 7/2x=40 | | 8y-18=3(y+3) | | x=17-15.5x | | 6-3x=10x-3 | | 1/10:1/8:1/6 | | x+2.5x=28 |

Equations solver categories